CHANGING SHOPPING HABITS OF RESIDENTS OF BUCHAREST AND THEIR ORIENTATION TOWARDS CONVENIENCE STORES - CĂTOIU, Iacob; NICULAE, Sabin; STĂNCULESCU, Anca Maria (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The purpose of this article is to examine the changes in consumer  shopping behavior as shoppers are turning their backs on the traditional weekly ‘big shopping’, and the average consumer now visits a supermarket or convenience store on average three times a week. In this context, we see supermarket and cash and carry - run convenience stores on Romanian market like Mega Image SHOP'nGO  and „La doi Pasi” are on the rise. This local, smaller shops are faster to get to and easier to navigate and they are bringing about a significant change in shopper habits.